Educational-assistencial integration in the care of wounds: report of experience - Aquino, Priscila de Souza; Moura, Lydia Meneses de; Florêncio, Maria Isabel Barbosa; Moura, Escolástica Rejane Ferreira (Rev Rene, 2006)
This is a descriptive-exploratory study. The data were collected on November, 2004 at a first level of reference unit system in Fortaleza, Ceará. The main aim of the research was to relate the development of a workshop as a space to reflection about the current conditions of the wound care service, ruled in the pedagogic proposal showed by Saul, in 1988. It consisted of educational-assistencial integration as mediative force for the promotion of the practice field transformation. Such experience can to be reproduced by other services and other students and groups of teachers who might be going through similar experiences, which is not unusual.